A Model of Transformative Da'wah in Thetransmigration Area of Nagari Sopan Jaya, Dharmasraya Regency - Moh Bashori Alwi Almanduri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
This article is a critical review of transformative dawah in Nagari Sopan Jaya, which has received little attention. In 1993, Nagari Sopan Jaya was one of the ex-transmigration areas. Religious knowledge is generally unknown in the transmigration community. The entity, on the other hand, can transform into a Sharia-aware individual and thus form a madani society civilisation. The goals of this study are as follows: 1) to describe the transformative da'wah model in transmigration areas; and 2) to see transmigration missionary dialogue as a tool for madani society development. This study employs a case study method with a descriptive explanatory approach. Data were gathered through observation, interviews, and a review of the literature. The results of the research show that the dawah of transformation is carried out in 3 stages; 1) planting monotheism and sharia awareness; 2) Islamic community development (ta'lim method); 3) Caring for the awareness of Muslims (takwin al ummah). Meanwhile, in the development of madani society there are 4 principles that must be upheld, namely moral and ethical principles (ruhama bainakum), social principles (khoiru ummah), political principles (siyasah), and brotherhood principles (ukhuwah Islamiyah, wathoniyah, and basyariyah). The four components have simultaneously been realized by the Sopan Jaya community so that it has grown into a madani society.